2023
DOI: 10.7759/cureus.37183
|View full text |Cite
|
Sign up to set email alerts
|

Adult Knowledge About Postoperative Complications of Rhinoplasty in the Western Region of Saudi Arabia

Abstract: BackgroundRhinoplasty, a prevalent cosmetic surgical procedure worldwide, is not exempt from associated risks and complications, as with any other surgery. In light of the surging demand for rhinoplasty amongst young adults, it is imperative to acknowledge that the procedure can engender various complications that can be classified as either early or late complications. Examples of early complications include epistaxis and periorbital ecchymosis, while late complications may manifest as enophthalmos or septal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…We found that 152 (20.6%) females were interested in rhinoplasty. Similar studies conducted in Saudi Arabia in different regions found that 25.7% in Riyadh [ 11 ] and 22.62% in the Western Region [ 12 ] were interested in rhinoplasty, which was consistent with our results. However, another study in Iran [ 10 ] among female high school students reported a higher percentage than ours, with 53.65 % of them interested in rhinoplasty [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found that 152 (20.6%) females were interested in rhinoplasty. Similar studies conducted in Saudi Arabia in different regions found that 25.7% in Riyadh [ 11 ] and 22.62% in the Western Region [ 12 ] were interested in rhinoplasty, which was consistent with our results. However, another study in Iran [ 10 ] among female high school students reported a higher percentage than ours, with 53.65 % of them interested in rhinoplasty [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…It aligned with our study, whereas 54.8% of participants who did not want to undergo rhinoplasty reported that they were satisfied with their nose shape, followed by concerns about the side effects of the surgery. This was consistent with the findings of the studies conducted in Riyadh [ 11 ] and the Western region of Saudi Arabia [ 12 ], where participants reported being happy with their nose as it was, followed by religious beliefs, concerns about side effects, and financial costs.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations